2016
DOI: 10.1159/000445074
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vaginal Oestriol Cream on Subjective and Objective Symptoms of Stress Urinary Incontinence and Vaginal Atrophy: An International Multi-Centre Pilot Study

Abstract: Aim: Subjectively and objectively assess stress urinary incontinence (SUI) symptoms before and after topical oestrogen therapy. Methods: A prospective study was performed in 3 centres in South-Africa, Australia and the Netherlands. Postmenopausal women with SUI were treated with topical oestriol cream for 6 weeks. The primary subjective outcome was the Patient's Global Impression of Improvement (PGI-I) scale. The primary objective outcome was vaginal pH. Secondary subjective outcomes were: the International Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…It showed the highest mean scores in the initial assessment, and presented a statistically significant decrease, demonstrating a subjective improvement in QoL. These results correlate with other studies of the effects of estriol on postmenopausal LUTS, mainly on irritative symptoms such as urinary urgency, frequency, and urge incontinence [17] [18].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It showed the highest mean scores in the initial assessment, and presented a statistically significant decrease, demonstrating a subjective improvement in QoL. These results correlate with other studies of the effects of estriol on postmenopausal LUTS, mainly on irritative symptoms such as urinary urgency, frequency, and urge incontinence [17] [18].…”
Section: Discussionsupporting
confidence: 86%
“…At a time when technology is overemphasized in Medicine, sustaining and enhancing QoL involves making healthcare more focused on people, and various studies have shown that the QoL of postmenopausal women with LUTS is seriously compromised in several contexts, such as at work, in relationships and their social lives [4] [6] [7]. The literature also suggests that vaginal estriol improves vaginal trophism and reduces LUTS, leading to a positive effect on QoL [9] [17] [18]. In the present study, the comparative analysis showed a decreased frequency of urinary symptoms and average scores in all domains of the KHQ questionnaire after the administration of vaginal estriol, indicating that the use of this hormone had a positive effect on the QoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SUI is the most common type of incontinence. The prevalence, estimated between 25% and 35%, increases with age and peaks during the fifth decade of life [12–17]. Overactive bladder (OAB) is characterized by urgency, increased urinary frequency, and nocturia, with or without incontinence, in the absence of relevant pathologies [18].…”
Section: Introductionmentioning
confidence: 99%
“…(7) More to the point, OAB is found with lower scores in overall health, quality of life, psychological well-being, sexual satisfaction, besides work productivity as opposed to patient controls. (8) In OAB, the onset of urgency incontinence is more likely to be followed by frequency and urgency owing to detrusor over activity. It has been shown detrusor over activity carries more effects on sexual function than urodynamic stress incontinence.…”
mentioning
confidence: 99%